The Importance of Individual Benefits – Understanding Patient Behaviour in E-Health Adoption - József Ráti; Ildikó Kemény; Péter Simon (Tržište)
Purpose – Advancements in telemedicine offer the potential to enhance healthcare efficiency, accessibility, quality, and environmental impact. However, the shift from traditional interpersonal healthcare to technology-mediated services necessitates a nuanced understanding of the factors influencing patient behavior. Design/Methodology/Approach – This research study extends the Technology Acceptance Model (TAM) to examine telemedicine adoption patterns. Beyond conventional TAM elements such as a positive attitude and technological readiness, the investigation scrutinizes the influences of social and individual benefits, alongside the impact of COVID-19 anxiety, specifically within the Central and Eastern European context. This methodological expansion and regional focus provide unique insights into the research domain. Utilizing regression analysis on data collected through an online survey, the study highlights the substantial influence of individual benefits and positive attitudes on the adoption of telemedicine technologies. Findings and implications – Perceived social benefits do not exhibit a statistically significant effect. These findings emphasize the need for tailored awareness initiatives that underscore the personal advantages of e-health solutions while addressing prevalent skepticism surrounding technology. Limitations – The findings are limited by the representativeness of the sample, as it over-represents young, educated women, urban residents, and individuals with a higher socioeconomic status. Originality – The insights derived from this study contribute to the growing body of knowledge aimed at facilitating a seamless integration of telemedicine technologies into healthcare frameworks within the targeted region.